VD_FINDINFO 107/2012/DCA vom 7. September 2012 - VD Tribunal cantonal (2012)
HONORAIRES, HONORAIRES CALCULÉS EN FONCTION DU RÉSULTAT POSITIF, MODÉRATION | 12 let. e LLCA, 45 al. 1 LPAv, 45 LPAv, 48 LPAv